Sendo médico em português: histórias vividas e narradas por dois médicos cubanos em atuação no Brasil - Silva, Suiane Bezerra da (Universidade Federal de São Carlos, 2023)
In 2016, I had my first opportunity to teach Portuguese lessons abroad to speakers of other languages. My students were Cuban doctors who were preparing for the international mission organized by the Ministries of Health and Education through the "Mais Médicos" Physician Recruitment Program. After the end of the Welcome and Assessment Module (MAAv), i.e., the course that physicians had to attend as a prerequisite for entering the program, I was interested in learning about the life these doctors were going to have in Brazil. Thus, this is a narrative research study, based on the theoretical-methodological perspective of Clandinin and Connelly (2000; 2015), whose overall objective is to gain further insights into the experiences narrated by two Cuban doctors working in Brazil. Particularly, my goals were to: a) analyze and discuss the experiences lived and reported in the narratives of the two doctors working in Brazil when they still had had little contact with Portuguese and b) identify and discuss the strategies the male and female Cuban physicians used for communicating with their patients during medical consultations. My motivation for conducting this study lies in my understanding of language as an important means of communication, interaction, and social inclusion. Thus, knowledge of the stories told by physicians can unveil the relationships and interactions between them, the Brazilian community, and the context of their host country, because to successfully perform their duties, the physicians would have to be able to communicate effectively with their patients. Also, everyday life would require practical resolutions, such as paying bills, going grocery shopping, taking a taxi, etc. Therefore, what the physicians reported on their interactions with Brazilians and their surroundings, on whether their presence was accepted or rejected, and on whether they could provide health care assistance, are strong narrative components that can account for a social and linguistic phenomenon that has manifested itself in our society. While discussing the experiences narrated by the participants, I addressed the following concepts: experience, as developed by educator John Dewey (1979); language variation, according to authors such as Bagno (2002), Calvet (2002), Gnerre (1998); language anxiety, an expression coined by MacIntire and Gardner (1991a, 1991b); personal knowledge, professional knowledge (ELBAZ, 1983; FENSTERMACHER, 1994; CLANDININ AND CONNELLY, 1985; 1988; 1995) and reflective practitioners (SCHÖN, 1983; 1992); primary health care attributes (STARFIELD, 2002), among others that I have considered to be relevant to the points raised. The physicians’ narratives that were selected to compose this study are stories of shared learning and knowledge, of communication strategies, of prejudice, among other meaningful aspects.

En 2016, tuve la oportunidad, por primera vez, de impartir clases de portugués para hablantes de otras lenguas fuera del Brasil. El público objetivo eran médicos cubanos que se estaban preparando para la misión internacional organizada por los Ministerios de la Salud y de la Educación, por intermedio del “Programa Mais Médicos”. Al terminar el Módulo de Acogida y de la Evaluación (MAEv), nombre del curso ofrecido a los médicos como requisitos previos para el ingreso al programa, tuve interés en saber cómo sería la vida de estos profesionales en Brasil. Así, esta es una investigación narrativa, anclada en la perspectiva teórico metodológica de Clandinin y Connelly (2000; 2015), cuyo objetivo general es comprender narrativamente las experiencias de dos médicos cubanos actuando en Brasil. Concretamente, deseé: a) analizar y discutir narrativamente las experiencias vividas y contadas por ambos trabajando en Brasil después del poco contacto con el portugués y b) identificar y discutir las estrategias del médico cubano y de la médica cubana para comunicarse con los pacientes y realizar visitas médicas. Los factores que dan forma a la justificativa en esta investigación están relacionados a mi entendimiento de la lengua como un importante factor de comunicación, de interacción y de inclusión social. De esta manera, conocer las historias relatadas puede permitir comprender las relaciones y las interacciones establecidas entre ellos, la comunidad brasileña y el contexto en el cual estaban insertados, una vez que el desarrollo de su función dependería de una efectiva comunicación con los pacientes; y la vida práctica exigiría resoluciones del cotidiano, como pagar las cuentas, ir al supermercado, pagar el taxi, etc. Por lo tanto, saber qué dicen los médicos acerca de las interacciones con los brasileños y con el medio, si su presencia fue recibida con receptividad positiva ou rechazo y si fue posible realizar sus funciones de asistencia a la salud son fuertes componentes narrativos para comprender un fenómeno social y lingüístico que se manifestó en nuestra sociedad. A partir de discusiones de las experiencias narradas por los participantes, traigo conceptos de experiencias, desarrollado por el educador John Dewey (1979); de variación lingüística, según autores como Bagno (2002), Calvet (2002), Gnerre (1998); de ansiedad con relación al uso de la lengua, expresión nombrada por MacIntyre y Gardner (1991a, 1991b); de conocimiento personal y profesional (ELBAZ, 1983; FENSTERMACHER, 1994; CLANDININ y CONNELLY, 1985; 1988; 1995) y de profesional reflexivo (SCHÖN, 1983; 1992); sobre los atributos de la Atención Primaria a la salud (STARFIELD, 2002) entre otros que comprendí seren pertinentes para dialogar con los puntos tratados. Las narrativas relatadas y escogidas para componer este trabajo son historias de aprendizajes y conocimiento compartido, de estrategias de comunicación, de prejuicio entre otros aspectos significativos.
Being a doctor in Portuguese: stories lived and told by two Cuban doctors working in Brazil
Keywords: Médicos cubanos; Programa mais médicos; Narrativas; Experiência; Pesquisa narrativa; Cuban doctors; "Mais Médicos" Physician Recruitment Program; Narratives; Experience; Narrative inquiry; Médicos cubanos; Programa más médicos; Narrativas; Experiencias; Investigación narrativa; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUA PORTUGUESA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA